2015
DOI: 10.1039/c5cc03945b
|View full text |Cite
|
Sign up to set email alerts
|

A one-step carbonization route towards nitrogen-doped porous carbon hollow spheres with ultrahigh nitrogen content for CO2 adsorption

Abstract: Nitrogen doped porous carbon hollow spheres (N-PCHSs) with an ultrahigh nitrogen content of 15.9 wt% and a high surface area of 775 m(2) g(-1) were prepared using Melamine-formaldehyde nanospheres as hard templates and nitrogen sources. The N-PCHSs were completely characterized and were found to exhibit considerable CO2 adsorption performance (4.42 mmol g(-1)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Captured CO 2 is typically utilized as a simple carbon-containing feedstock (C1) for generating industrially relevant organic molecules [ 1 ]. Numerous porous solid adsorbates such as zeolites [ 2 ], metal-organic frameworks [ 3 ], and mesoporous carbons [ 4 , 5 ] have been proposed for the effective capture and processing of CO 2 . Some research groups have reported that nitrogen-doped carbon materials interact more effectively with CO 2 than inactive carbon materials do [ 4 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Captured CO 2 is typically utilized as a simple carbon-containing feedstock (C1) for generating industrially relevant organic molecules [ 1 ]. Numerous porous solid adsorbates such as zeolites [ 2 ], metal-organic frameworks [ 3 ], and mesoporous carbons [ 4 , 5 ] have been proposed for the effective capture and processing of CO 2 . Some research groups have reported that nitrogen-doped carbon materials interact more effectively with CO 2 than inactive carbon materials do [ 4 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous porous solid adsorbates such as zeolites [ 2 ], metal-organic frameworks [ 3 ], and mesoporous carbons [ 4 , 5 ] have been proposed for the effective capture and processing of CO 2 . Some research groups have reported that nitrogen-doped carbon materials interact more effectively with CO 2 than inactive carbon materials do [ 4 8 ]. Furthermore, they are also expected as promising electrocatalysts for CO 2 and oxygen reduction reaction [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among free N-doped porous carbons, HKC-800-1 shows superior CO 2 adsorption of 217 mg/g relative to commercial activated carbon (123.2 mg/g), 48 OMC (132 mg/g), 49 OM-CNS (175.1 mg/g), 50 CA-HC200 (198.4 mg/g), 51 and PC500 (190.5 mg/g), 52 and it was also comparable with PMMC-800 (237.6 mg/g), 53 NET2-2-700-2 (228.8 mg/g), 54 and L2600 (233.2 mg/g). 36 Compared with these N-doped porous carbons, such as salt-templated carbons with arginine (147.8 mg/g), 56 FC4 (178.2 mg/g), 57 OTSS-1-550 (191.4 mg/g), 58 N-PHCS-900 (194.5 mg/g), 59 microporous carbon from fern leaves (198.9 mg/g), 60 and PDA 0.3 /MA 0.7 -2 (202.4 mg/g), 62 the CO 2 uptake of our porous carbons was also decent. HKC-800-1 was also comparable with c-CBAP-1N (223.5 mg/g), 66 H150-800 (228.1 mg/g), 67 NPC500 (235.8 mg/g), 52 Bamboo-1-973 (233.2 mg/g), 33 and AC-KOH-W-2-700 (237.6 mg/g).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, this method has some disadvantages, such as high energy consumption and equipment corrosion . In recent years, CO 2 adsorption from flue gas by solid porous materials has attracted much attention. , CO 2 capture by porous sorbents is a highly efficient, energy-saving, and regenerable technology. , Several porous sorbents including porous carbon, zeolites, porous silica, metal–organic frameworks (MOFs), and porous polymers have been reported. Among these porous materials, porous carbon has been regarded as an outstanding candidate for CO 2 capture because of the large surface area, good stability, low cost, and tunable textural features. However, the adsorption performance of porous carbon is limited by the moderate interaction between the CO 2 molecule and the carbon surface. Therefore, it is necessary to develop an effective method to promote the CO 2 capture ability of porous carbon.…”
Section: Introductionmentioning
confidence: 99%